POLA RUANG PERMUKIMAN DI SEKITAR KAWASAN KERATON SURAKARTA DAN KERATON KASEPUHAN - Kustianingrum, Dwi; Putra, Wahyu Buana; Adityanto, Muhammad Miko; Zuhair, Azhar Fairuz; Azdaffa, Ahmad Naufal (Jurnal Arsitektur ZONASI, 2023)
Abstract: The palace is the area where the ruler lives. In the everyday sense, it is the palace of the rulers in Java. The palace is also a palace which has a high philosophical, religious, and cultural meaning. The presence of the Walisongo in the archipelago has an impact not only seen in the decorations/patterns on the palace buildings, but also in the spatial layout, landscape patterns within the palace complex and around the palace. The palace as a symbol of the power building in the end, gave an influence on the development of the pattern of space around it. This study aims to detect land use, circulation and open space around the Kasepuhan Cirebon and Surakarta Palaces. These two palaces were used as objects of research because they were considered the same scope and could represent the locations of West Java and Central Java. Descriptive analysis is the study methodology employed. As a result of these two palaces: (1) land use, both have in common, namely housing, trade and green zones, (2) circulation in both Kasepuhan palaces has a grid pattern, only in Kasepuhan palace it is mixed with radials, and has surrounding functions as trade and services, (3) open space, in the Surakarta Palace there are Lor and Kidul squares for community activities, tourism and markets, while in the Kasepuhan palace there is a Balong Darmaloka open space for tourism and an open space for ceremonies and markets.the Kasepuhan Cirebon and Karaton Surakarta. These two palaces were used as research objects because they were considered to have the same scope and could represent the locations of West Java and Central Java.Keywords: Space Pattern, Karaton, Land Use, Circulation, Open SpaceAbstrak: Keraton merupakan wilayah penguasa tinggal. Dapat diistilahkan istana penguasa di wilayah tanah Jawa. Keraton adalah istana yang berarti secara filsafat, kebudayaan, dan keagamaan yang tinggi. Hadirnya para Walisongo di Nusantara memberikan dampak tidak hanya terlihat di ragam hias/corak pada bangunan-bangunan keraton, akan tetapi juga pada tata ruang, pola lanskap di dalam komplek keraton maupun di permukiman sekitar keraton. Keraton sebagai simbolis bangunan kekuasaan pada masa lampau, memberi pengaruh terhadap perkembangan pola ruang disekitarnya. Penelitian ini bertujuan mengidentifikasi tata guna lahan, sirkulasi dan ruang terbuka  yang terdapat di permukiman sekitar keraton Kasepuhan Cirebon dan Keraton Surakarta. Kedua keraton ini dijadikan objek penelitian karena dianggap mempunyai lingkup yang sama dan dapat  mewakili lokasi daerah Jawa Barat dan Jawa Tengah. Penelitian ini menggunakan metode deskriptif analistis. Sebagai kesimpulan pola permukiman di sekitar kedua keraton ini: (1) Tataguna lahan, keduanya mempunya kesamaan yaitu zona perumahan,, perdagangan dan jasa dan zona hijau, (2) Sirkulasi di kedua  keraton Kasepuhan  mempunyai pola grid, hanya yang di Keraton Kasepuhan bercampur dengan radial, dan mempunyai fungsi disekitarnya sebagai perdangangan dan jasa, (3) Ruang/ Area terbuka, Kompleks Keraton Surakarta memiliki Alun-alun Lor dan Kidul yang berfungsi sebagai tempat aktifitas masyarakatnya, wisata dan pasar, adapun di Komplek Keraton Kasepuhan terdapat ruang terbuka Balong Darmaloka untuk wisata dan ruang terbuka alun-alun untuk upacara dan pasar.Kata Kunci: pola ruang, keraton,tata guna lahan, sirkulasi,ruang terbuka